Contagion-Based Chatbot Usage Intention: Synthesizing Technology Adoption And Social Contagion Theory - Rumetor, Meilisa; Thea Sajow, Gabriela; William Niode, Daniel; Rinawati Simanjuntak, Evi (Journal of World Science, 2024)
Chatbots have become transformative technology in the banking industry. However, there is still a knowledge gap in understanding the influence of social contagion on chatbot user behavior. This research aims to identify and analyze the intention to use chatbots based on the synthesis of technology adoption and social contagion theories. The research method used is quantitative, employing a survey approach and collecting data through online questionnaires from 300 chatbot users in private banks in Manado. Data analysis was conducted using smartPLS. The research results indicate that factors such as Perceived Effectiveness, Perceived Ease of Use, and Coercive Pressure significantly influence users' intention to continue using chatbots. However, normative pressure and mimicry do not have a significant impact. These findings provide an important contribution to theoretical understanding and practical application in the sustainable use of chatbots in the banking industry, which can assist banks in designing more effective marketing strategies and services.